Analysis of Influence of Independent and Board of Commissioners Managerial Ownership of Return on Assets (ROA) at PT. Adaro Energy Tbk, Period 2016-2020 - Roswaty . (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2023)
The purpose of this study was to determine the significance of the influence of independent commissioners and managerial ownership on ROA. This research was conducted at the Adaro Energy company in the 2016-2020 period. The data analysis technique used is multiple linear regression analysis using Eviews 10 software. Based on the results of the F test the first analysis obtained a significance value of F of 0.046390 <0.05. Then the regression has a significant effect so that it can be concluded that there is a significant simultaneous effect of the Independent Board of Commissioners and Managerial Ownership variables on Return on Assets. Based on the T test results obtained partial results of the Independent Board of Commissioners on ROA with a significance value of 0.2293> with a Coefficient regression value (-0.085447) means that the Independent Commissioner has a negative and not significant effect on ROA. That the size of the proportion of the independent commissioners in the company does not guarantee that the company's profitability is getting better and there is no fraud in the company's financial reporting. Based on the T test results obtained partially Managerial Ownership probability level of 0.0866> α 5% with Coefficient regression value (-0.692288) means Managerial Ownership has a negative and not significant effect on ROA. This situation occurs because of the small proportion of share ownership in the sample companies so that it has not been able to increase ROA.